An Evaluation of Habitat Connectivity of Conservation Subdivisions in Waukesha County, Wisconsin - Nixon, Kristi; Wells, Ana (My University, 2016)
Conservation subdivisions are designed to preserve at least 50% of their buildable land as open space with the purpose of protecting wildlife habitat and wildlife corridors. Yet, several conservation subdivisions (CSD) in Waukesha County, Wisconsin, have not met this minimum threshold; moreover, these subdivisions may be isolated from surrounding wildlife habitats and corridors, potentially impairing wildlife mobility. We want to evaluate the conservation value of the CSs by quantifying the effect that the amount of preserved open space and their connectivity to surrounding habitats have on the ability of wildlife species to move across the landscape. We will select species with diverse habitat requirements, sensitive to changes in habitat and that are of conservation concern in the region. To evaluate connectivity, we will produce landscape crossing resistance maps utilizing information of species' habitat suitability and movement capabilities. Layers of the conservation subdivisions will be overlayed and scored based on the results of the resistance map output, as well as their percent open space.
Includes maps, figures, tables, bibliography
Keywords: Habitat; Wildlife; Conservation; Waukesha County; Wisconsin